Antimicrobial activity of β-Sitosterol Isolated from Kalanchoe tomentosa leaves against Staphylococcus aureus and Klebsiella pneumonia - Anwar, Risyandi; Sukmasari, Susi; Siti Aisyah, Lilis; Puspita Lestari, Faridia; Ilfani, Delia; Febriani Yunand, Yenny; Diki Presyta, Pebrian (Asian Network for Scientific Information, 2022)
Background and Objective: Fresh K. tomentosa leaves obtained from Bandung, Indonesia was extracted using n-hexane followed by serial dichloromethane maceration. Material and Method: N-hexane and ethyl acetate were used to separate the dichloromethane extract using Vacuum Liquid Chromatography and the isolated compounds were recrystallized with n-hexane. Result: 37 mg of dichloromethane extract was obtained from the extraction process. Recrystallized compound isolates were identified as stigmast-5-en-3ꞵ-ol or β-sitosterol. Both dichloromethane extract and β-sitosterol isolated compounds showed strong bacteriostatic activity against S. aureus with MIC=15.63 µg/mL and 7.81µg/mL, and K. pneumonia with MIC=7.81µg/mL and 31.25µg/mL, respectively. However, only dichloromethane extract exhibited a bactericidal effect (7.81 µg/mL). Conclusion: The pure β-sitosterol compound was isolated from K. tomentosa dichloromethane extract. Both the dichloromethane extract and the isolated β-sitosterol compound had antibacterial effects against S. aureus and K. pneumonia